Analisis Deskriptif Faktor-Faktor yang Mempengaruhi Pembatalan Perkawinan di Pengadilan Agama Bekasi - Suprihatin Suprihatin (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
The purpose of this study is to determine the factors that influence the cancellation of marriage and to know the benefits or consequences of the cancellation of marriage. The method used in this research is qualitative method. The results of this study, is that the factors that affect the cancellation of marriage namely internal factors and external factors. Internal factor is something that comes from within the marriage itself this husband as Petitioner of marriage and wife invalidation as Respondent caused by identity, admitted still a girl have never married but actually have been married to other man, The applicant felt cheated and mistaken. while the external factor is something or cause that comes from outside the marriage where an elder sister who filed for the cancellation of her sister's marriage, resides as Petitioner and her sister as (Petitioner II) and husband (Respondent I) this is due to falsify the identity and guardian who is not entitled to marry off. Based on the above data can be found the element of protection of rights and maslahah for individuals who do marriage from the injustice of other parties.